As contribuições de Alexander Fleming para o estudo da imunologia natural: 1908-1921 - Kawakami, Deisy Sunae (2009)
On the turn of the twentieth century, several scientists were investigating infectious diseases. The aim of this research is to rebuild the path followed by Alexander Fleming (1881-1955) in his studies on microbiology, from 1908 to 1921, when he identified an enzyme related to the natural immunology of living beings. This dissertation contains an introduction and five chapters. Chapter 1 deals with Fleming s first bacteriological investigations, in cooperation with Almroth Wright (1861-1947). Besides that, it deals with Fleming s prescriptions for skin infections. Chapter 2 analyses Fleming´s contributions concerning the SALVARSAN therapy. Chapter 3 presents Fleming´s research on the treatment of infected injures got during the First World War, as well as, the experiments on microorganisms performed by him. Chapter 4 describes Fleming s research on secretions and tissues, concerning the identification of an important enzyme related to the natural immunology. Chapter 5 provides some final remarks on the subject. This study showed that Fleming was very cautious in methodological terms. It led to the conclusion that although Fleming had been trained under Wright and several of his contributions were part of a collective work, this was not the case concerning the identification of lysozyme. This Fleming´s original contribution changes the view that was accepted at that time